The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1530/ec-19-0366
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance associates with hepatic lobular inflammation in subjects with obesity

Abstract: Purpose Obese subjects with nonalcoholic fatty liver disease (NAFLD) are more prone to develop additional metabolic disturbances such as systemic insulin resistance (IR) and type 2 diabetes. NAFLD is defined by hepatic steatosis, lobular inflammation, ballooning and stage of fibrosis, but it is unclear if and which components could contribute to IR. Objective To assess which histological components of NAFLD associate with IR in subjects with obesity, and if so, to what extent. Methods This cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…It has been observed that the CB2 Q63R variant is also present in subjects with NAFLD and is associated with high-grade inflammation in the liver [103]. Since CB1 and CB2 receptors are also expressed in this organ, their regulation could be important for reducing liver impairments, as demonstrated also by Coppola et al in patients with chronic hepatitis C (HCV) [103,104,105,106,107]. In collecting all of this evidence, it is possible to suggest the EC system as pathological marker and pharmacological target to manage, not only the obesity-associated inflammation, but also its secondary complications.…”
Section: The Ec System In Obesity and Fatty Liver Diseasementioning
confidence: 99%
“…It has been observed that the CB2 Q63R variant is also present in subjects with NAFLD and is associated with high-grade inflammation in the liver [103]. Since CB1 and CB2 receptors are also expressed in this organ, their regulation could be important for reducing liver impairments, as demonstrated also by Coppola et al in patients with chronic hepatitis C (HCV) [103,104,105,106,107]. In collecting all of this evidence, it is possible to suggest the EC system as pathological marker and pharmacological target to manage, not only the obesity-associated inflammation, but also its secondary complications.…”
Section: The Ec System In Obesity and Fatty Liver Diseasementioning
confidence: 99%
“…The lipid aggregation in the adipose tissue up‐regulates the inflammatory cytokines, particularly the (TNF‐ α ) which triggers inflammation through the c‐Jun N ‐terminal kinase (JNK) and nuclear factor‐kappa B (NF‐κB) signaling pathways [12] . Overproduction of the TNF‐ α within the adipose tissue of obese rats not only induces lipogenesis and triglycerides accumulation but also, activates phosphorylation of the insulin receptor substrate‐1 (IRS‐1) initiating insulin resistance [13] …”
Section: Resultsmentioning
confidence: 99%
“…They suppress the sterol‐regulating element‐binding protein‐1 (SREBP‐1), stimulate the AMP‐activated protein kinase (AMPK), and peroxisome proliferator‐activated receptor alpha (PPAR‐ α ) triggering fatty acid oxidation and thus improving insulin sensitivity [13] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations